Gerak Sehat Jalin Silaturahmi: Aktivitas Senam Sebagai Wadah Interaksi Sosial Masyarakat Kelurahan Tampan Pekanbaru - Hefi, Muhammad Refriksan; Tuljannah, Sakina Wirda; Husain, Muthia Dinda; Berluscony, Vincentius Febrio; Tea, Shofia Triana; Putri, Andini Rizki; Pratama, Gusti Rangga; Gurusinga, Jeselia Fransiska Br.; Kesuma, Andriyan; Taqwa, Syafira Alyada; Bone, Muhammad Aditya; Hermawan, Chandra; Yesicha, Chelsy (Civiliza Publishing, 2025)
Gymnastics is a physical activity that is beneficial for physical health while acting as a means of social interaction that strengthens relationships between residents. This service program aims to describe the role of gymnastics as a forum for community social interaction on Jalan Jambu Mawar, Tampan Village, Pekanbaru. The activity was carried out using a participatory method during the Independent Learning Real Work Lecture (Kukerta) Independent Campus, Faculty of Social and Political Sciences, University of Riau. Involving 30 participants dominated by housewives, as well as Donni's Club as facilitators. Data was collected through participation, interviews and documentation. The results showed that routine gymnastics led to light conversations, information exchange, and strengthened social relationships, while improving physical fitness and awareness of healthy living.